Հայերենի բառապաշարի ուսուցումը օտարներին - Տիոյան, Ս. Կ. (Մանկավարժ հրատ․)
В статье представлен способ обучения словарного состава армянского языка, который основан на методе ’’небольшое количество, но основательное обучение’’. Это наиболее употребительные слова и их наиболее распространенные значения. Принято во внимание как частиречная принадлежность слова, так и его принадлежность к различным семантическим группам. The article presents a mode of teaching of the vocabulary of the Armenian, which is based on the method - a small number, but good teaching. These words are the most usable ones of the Armenian language with their common and the most spread meanings. The parts of speech of these words and meanings belonging to different semantic groups are taken into account.
Keywords: Ուսուցման և դասավանդման մեթոդիկա